PERANAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SD NEGERI 018 HARAPAN TANI KECAMATAN KEMPAS KABUPATEN INDRAGIRI HILIR RIAU - jurnalmap map (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2022)
This study aims to provide an overview of the principal's leadership in improving teacher performance at SDN 018 Harapan Tani, Kempas District, Indragiri Hilir Regency, Riau. This research is a form of field research (field research) which is descriptive qualitative, using several approaches, namely, on the pedagogical, sociological, psychological and managerial. The results showed that the leadership role of the head of SDN 018 Harapan Tani in carrying out his duties with full responsibility, with the aim of improving teacher performance, by taking a normative approach or motivating teachers to always work according to their duties. The procedure desired by the principal in improving teacher performance is to carry out supervision with an approach of deliberation, communication, planning, coordination and evaluation, with this application finally all intentions will be realized. Based on the results of the study, it can be illustrated that to support all principals' programs in improving performance, external and internal factors, facilities and infrastructure, methods and programs.